A.L. Drayton papers - Drayton, A. L.
Diary (1863 January 16-June 26) kept while on board the C.S.S. Florida and the S.S. brigantine Clarence.
Seaman.
Collection material in English.
Keywords: Florida (Cruiser); Clarence (Ship); Ship's papers -- 19th century; Confederate States of America. -- Navy; United States -- History -- Civil War, 1861-1865.; Sailors